2016
DOI: 10.1177/229255031602400210
|View full text |Cite
|
Sign up to set email alerts
|

Shared medical appointments as a new model for carpal tunnel surgery consultation: A randomized clinical trial

Abstract: These results support the use of shared appointments for large-volume, low-variation surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…18,21,23 Four studies reported the education levels of their participants, with a majority of attendees having greater than high school education as their highest level of education (range 50.1% to 100%) (three studies) and one trial reported the majority of attendees having high school education or less as their highest level of education (100%). 16,21,23,25 Two studies reported their participants work demographics, with both reporting a minority of patients being employed (6.3% and 17%). 18,23…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…18,21,23 Four studies reported the education levels of their participants, with a majority of attendees having greater than high school education as their highest level of education (range 50.1% to 100%) (three studies) and one trial reported the majority of attendees having high school education or less as their highest level of education (100%). 16,21,23,25 Two studies reported their participants work demographics, with both reporting a minority of patients being employed (6.3% and 17%). 18,23…”
Section: Resultsmentioning
confidence: 99%
“…22 Of the four studies that measured patient satisfaction, there was no significant difference between SMA and usual care. 21,23,24,25…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional options to explore may include group medical appointments 31–34 or shared education classes 35 tailored to individuals considering MaPGAS, which would offer a moderated forum for discussing concerns, sharing experiences, and addressing questions in a supportive environment. Increased discussion of complications and the provision of photographs of surgical outcomes during consultations can further aid in setting realistic expectations and provide further decision support.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Shared medical appointments are most commonly used in primary care settings, but they have been explored in other subspecialties, including some surgical practices. 5 This model has been studied in a limited number of chronic neurologic conditions, including neuromuscular disorders, 6 Parkinson disease, 7 and neuropathic pain. 8 These pilot studies yielded mixed results but suggested that these visits improve patient-reported outcomes and physician productivity.…”
Section: O N L I N E F I R S Tmentioning
confidence: 99%